Migraine With Aura Is Related to Delayed Motor Control Reaction and Imbalance Following External Perturbations - Carvalho, Gabriela F.; Luedtke, Kerstin; Pinheiro, Carina F.; Moraes, Renato; Lemos, Tenysson W.; Bigal, Marcelo E.; Dach, Fabiola; Bevilaqua-Grossi, Debora (Frontiers in Neurology, 2021)
Background: It is evidenced that migraineurs present balance deficits. However, the balance recovery following unexpected ground perturbations, which reflect conditions of everyday activities, has not been investigated in this population. Aim: We aimed to assess the reactive postural responses among patients with migraine with and without aura, chronic migraine, and controls. We further aimed to assess the factors associated with greater self-report of falls. Methods: Ninety patients diagnosed by headache specialists were equally classified into three migraine subgroups according to the presence of aura and chronic migraine. Thirty controls were also recruited. All participants underwent the motor control test (MCT) and adaptation test (ADT) protocols of dynamic posturography tests (EquiTest®, NeuroCom, USA). Clinical and headache features and information of falls in the previous year, fear of falling, and vestibular symptoms were also assessed. Results: Patients with aura presented greater sway area in most of the MCT conditions than the other three groups (p=0.001). The aura group also presented delayed latency response after perturbations compared to controls and patients without aura (p<0.03). In the ADT, a greater sway area was observed in patients with aura than in groups without aura, chronic migraine, and controls (p<0.0001). The MCT and ADT sway area, the frequency of aura, and the fear of falling explained 46% of the fall in the previous twelve months. Conclusion: Patients with aura exhibited greater delay and sway area after unexpected ground perturbations than controls and other migraine subgroups, which are related to the reported number of falls.